Enhancing Tomato (Lycopersicon esculentum Mill.) Growth in a Green House Using NPK Fertilizer Coated with Endospore-Forming Bacillus - Hindersah, Reginawanti; Fitriatin, Betty Natalie; Setiawati, Mieke Rochimi; Suryatmana, Pujawati; Risanti, Rara Rahmatika; Dewi, Yeni Wispa (Fakultas Pertanian Universitas Padjadjaran, 2025)
Long-term use of NPK composite fertilizers mixed with biofertilizers, including spore-forming Bacillus rhizobacteria, can improve plant quality and growth. This study aims to analyze Bacillus’s growth and spore production in chemical-liquid growing media and to observe the effects of Bacillus-coated NPK formulas (BCN) on the growth of tomatoes in potted Andisol and the Bacillus population in the rhizosphere. The evaluation of Bacillus growth was conducted in the laboratory whereas the effect of the BCN was conducted as a pot experiment in a Randomized Block Design. The treatments included recommended dosage of NPK 16-16-16, liquid inoculant of Bacillus consortium, BCN-C, and BCN-G formulas with 100%, 75%, and 50% of the recommended dosage, respectively. Control plants were not treated with fertilizer. Laboratory assay verified that Yuniarti’s medium supported Bacillus-consortium growth and produced the highest Bacillus vegetative cells and spores. The BCN application significantly increased plant height, number of leaves, root length, and tomato biomass compared to the control up to 6 weeks after planting. Three-quarters of the dosage of BCN-C and BCN-G gave the best growth of tomatoes. Introducing BCN and conventional NPK did not change the population of Bacillus vegetative and spore form in the rhizosphere. Results indicate that BCN can replace conventional NPK 16-16-16 fertilizer for tomato plants in Andisol soil order.